New species of the genus Ontholestes Ganglbauer, 1895 (Coleoptera: Staphylinidae: Staphylininae) from Yakutia - Smetana, Aleš; Shavrin, Alexey V. (Zootaxa, 2013)
Recently, the junior author had an opportunity to study material of Staphylinidae, which was given to him by the Yakutian entomologist Dr. Sargylana Nogovitsyna (Institute of Biological Problems of Cryolithozone, Yakutsk, Russia). Three species of the genus Ontholestes Ganglbauer, 1895 were included in this material from South-western and North-eastern Yakutia (Republic of Sakha, Russia): O. inauratus Mannerheim, 1830, O. murinus (Linnaeus, 1758) and one additional, new species in three specimens (Shavrin et al. 2008), all from north-eastern part of Yakutia (Cherskiy Mts., Suntar-Khayata Mts.). Subsequently, during one of the annual Meetings on Biology and Systematics of Staphylinidae, the junior author presented two males of this new species to the senior author who concurred that it is a new species. The goal of our paper is to give the description of this new species.